Acupuncture in the Treatment of Chronic Low Back Pain - Wong, Michael J (DALHOUSIE MEDICAL JOURNAL, 2012)
Chronic low back pain is a costly medical complaint in Canada and other industrialized nations. In most cases,the specific etiology of the problem cannot be clearly identified, and treatment success is variable. As such, aconsiderable proportion of patients with chronic low back pain turn to acupuncture as an alternative to conventionalmedical therapy. This review aims to synthesize current clinical evidence for acupuncture as a treatment for chroniclow back pain, by summarizing the 2005 Cochrane systematic review on acupuncture and low back pain, along withmore recent systematic reviews. The existing literature suggests that acupuncture is a useful therapy for chronic lowback pain patients, despite a currently incomplete understanding of its physiological basis.